Gluon radiation beyond Poisson using MHV techniques - Rasoanaivo, Andriniaina Narindra (Department of Physics, 2018)
For the first time, MHV techniques are applied to radiative energy loss processes in QCD. First, we provide a pedagogical introduction to MHV techniques with explicit computational example on qq → ɡɡ cross section and splitting functions which reproduces known results. Next, we derive the multiple photon emissions current to reproduce the Poisson distribution of photon radiated from a high energetic quark. Then we derive the equivalent current for the case of multiple gluon emissions in vacuum. We then use the previous result to compute the two gluon correlation. We also study the radiation current induced from a change in the color state of an energetic quark: we start with the case of 1, 2, and 3 gluon induced radiations and then conjecture the analytic expression for n gluon emissions. We then prove this conjecture for the case where the emitted gluons are symmetric and antisymmetric under gluon permutations.